ANALYSIS IN THE POSSIBLE FACTORS AFFECTING ACCEPTANCE AND HESITATION TOWARDS ONLINE SHOPPING - Bangug, Jamille Wayne; Verbo, Charise; Acidera, Rizza Mae; Castillo, Ranny; Languido, Mica Mae; Butac, Ciahara Joy; Rabago, Juvilie Jane; Halog, Jahna Mae; Esteban, Criselle Joy; Paiste, Jovelyn (International Journal of Arts, Sciences and Education, 2022)
ABSTRACT: This research aims to identify the possible factors affecting acceptance and hesitation towards online shopping and at the same time to identify safety precautions in online shopping. Thematic analysis was used and the researchers analyzed and interpret the gathered data through open-ended questions in order to draw themes and creates meaning. The researchers used Purposive sampling which is a non-probability sample chosen based on the population’s characteristics and its objective. The study have 15 participants who are a student/shopper from Isabela State University-San Mariano Campus. The study results suggest that there are three factors why students/shoppers still prefer to buy online, namely; it is Low-cost, Relieves stress and Therapeutic, and Accessibility and Convenience. The study also found out that there is still hesitations in buying online which is because of scams and other issues. Lastly, safety precautions is also identified such as reading feedbacks and be cautious and vigilant in buying products online. The educational implications of online shopping were discussed.